Excitation of Surface Plasmons by Inelastic Electron Tunneling - Liu, Lufang; Xu, Yue; Zhu, Jiajie; Wang, Pan; Tong, Limin; Krasavin, Alexey V. (Frontiers in Physics, 2020)
Surface plasmons are usually excited by diffraction-limited optical methods with the use of bulky optical components, which greatly limit the miniaturization and chip-scale high-density integration of plasmonic devices. By integrating a plasmonic nanostructure with a tunnel junction, plasmonic modes in the nanostructure can be directly excited by low-energy tunneling electrons, with the advantages including ultra-small footprint and ultra-fast speed. In this mini-review, the recent progress in the electric excitation of localized and propagating surface plasmons by inelastic electron tunneling is overviewed.